1985
DOI: 10.1159/000242156
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Changes in Fetal Hemoglobin, Oxygen Affinity and 2,3-Diphosphoglycerate in Previously Transfused Preterm Infants

Abstract: We observed a temporary rise in the percentage of fetal hemoglobin (HbF%) in small preterm infants after cessation of frequent replacement transfusions. We prospectively studied 10 very low birth weight infants, who received frequent transfusions in the first several weeks of life, to determine the influence on oxygen affinity (P50). After cessation of frequent transfusions, those 5 infants whose HbF% increased to the highest values (mean 58%) had a lower oxygen affinity (P50 = 23.3 Torr,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This study included more blood samples and data points for HbF and related SO 2 measurements to compare the hemoximeter readings against the HPLC in neonates. Following the blood transfusions, HbO 2 dissociation curves were right-shifted in these neonates [17,20], and we substantiated these right-shifted S-curves with decreased blood and clinical oximeter oxygen saturation readings in relation to the same ranges of PaO 2 values. In relation to the critical PaO 2 value of 50 mm Hg (for the critical value for hypoxemia), following the blood transfusions, arterial HbO 2 was 1% lower (91% to 90%), SaO 2 was 0.5% lower (94 to 93.5%), and SpO 2 was 1% lower (95% to 94%), when compared to the measurements prior to the blood transfusions.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This study included more blood samples and data points for HbF and related SO 2 measurements to compare the hemoximeter readings against the HPLC in neonates. Following the blood transfusions, HbO 2 dissociation curves were right-shifted in these neonates [17,20], and we substantiated these right-shifted S-curves with decreased blood and clinical oximeter oxygen saturation readings in relation to the same ranges of PaO 2 values. In relation to the critical PaO 2 value of 50 mm Hg (for the critical value for hypoxemia), following the blood transfusions, arterial HbO 2 was 1% lower (91% to 90%), SaO 2 was 0.5% lower (94 to 93.5%), and SpO 2 was 1% lower (95% to 94%), when compared to the measurements prior to the blood transfusions.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, HbA blood should be transfused slowly and SO 2 measurements should be monitored closely following blood transfusions in neonates [18,19]. For functional SO 2 measurements in relation to the HbF changes in neonates, 2 previous small studies (n=10, and 11) have reported the rightshifting HbO2 dissociation curves following blood transfusions using P 50 measurements [17,20]. Widespread clinical pulse oximeter (SpO 2 ) readings had been reported in relation to the PaO 2 values without providing a precise HbO2 dissociation curve for neonates [21] in relation to the clinical PaO 2 ranges of 50-75 mm Hg [22], related SO 2 measurements need to be established for neonates, accounting for the effects of HbF levels.…”
Section: Introductionmentioning
confidence: 99%
“…These changes and their timing are consistent with previous observations. 10,11 As the percentage of Hb F increased after transfusion therapy was completed, there was no subsequent increase observed in MCV. This is not unexpected given the gradual fall in MCV that is known to occur postnatally in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal adaptations to survive this profound hypoxia include: I ) HbF, which shifts the oxygen dissociation curve to the left, increasing blood oxygen carrying capacity (4,5); 2) elevated Hb concentration enhancing tissue oxygen transport (22,23); and 3) the "double Bohr effect," which regulates transplacental gas exchange, enhancing oxygen uptake by the fetal blood (21). Some of these adaptations, such system independent of respiratory acidosis or alkalosis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-induced acidosis, determined by the extent of tissue hypoxia (4,5), is primarily caused by anaerobic ATP hydrolysis and anaerobic glycolysis secondary to severe 0 2 reductions (6)(7)(8). Persistent fetal adaptations to the hypoxic environment in utero may influence the neonate's ability to cope with hypoxia postpartum.…”
mentioning
confidence: 99%